Methodological Bases of Formation of Chemical Concepts in Pupils in School from Chemistry Course - E.Shamurodov; Sh.Sharipov; G’.Sharifov; X.Juraev; J.Bazorova (Zien Journals, 2021)
This article presents the theoretical basis of the methods of applying the experience of pedagogical skills of the pedagogical teacher in the teaching of chemistry
Keywords: modernization; technology; pedagogical technology; technology of educational process